Development of Student’s Worksheet Integrated with Predict Observe Explain (POE) Model to Facilitate Students' Critical Thinking Skills - Vina Elviana; Putri Dwi Sundari; Hufri Hufri; Hidayati Hidayati (Postgraduate, University of Mataram, 2024)
Critical thinking ability is one of the important skills that need to be improved to face the 21st century. In learning physics, appropriate teaching materials are needed and can improve students' critical thinking skills so that students can increase their learning independence. The purpose of this research is to develop student worksheets integrated with the Predict Observe Explain (POE) learning model to facilitate student's critical thinking skills. The type of research used in this study is Research and Development (R&D) with the Borg and Gall model modified into six stages, namely potential and problems, data collection, product design, product validation, product revision, and product trial. The research instruments used were expert validation sheets, teacher practicality sheets, and student practicality sheets. The data analysis technique used was descriptive statistics. The results of this study are the average value of the validity of the student worksheet product is 0.82 which is categorized as valid, and the average value of practicality according to the teacher is 98% and the average value of practicality according to students is 90% with a very practical category. therefore, the use of student worksheets integrated with the POE model is valid and practical in learning physics.